Redesign of Cover Lower Dies on Compaction Tool in Sealface Manufacturing Based on Powder Metallurgy Process - Media, Riona Ihsan; Purnawarman, Otto; Budiarto, Hanif Azis; Caesario, Daffa (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
The cover lower dies constitute a vital component of the ejector compaction tool system employed in the powder metallurgy process for sealface production. However, a failure occurred in the compaction process, leading to the deformation of the component after the production of more than eleven sealfaces. This study investigates the ejector compaction tool system, with a specific focus on the cover lower dies, aiming to optimize the tool's construction. Employing the Pahl & Beitz design methodology, the research encompasses discussions with previous researchers, observation of existing tools, disassembly of current tools, and simulation analysis. Emphasizing static analysis to assess stress, deflection, and safety factor values, the research aims for a safety factor exceeding 2.00 in the redesigned cover lower dies. The optimal solution involves changing the material to AISI D2 with a hardness of 62 HRC, modifying the cover lower dies thickness by 13mm, and increasing springs and retained pins from 2 to 4 pieces. Consequently, the redesigned ejector compaction tool system is deemed operationally safe, signifying a successful improvement in its construction for enhanced reliability and performance.